Diversity and Distribution of Ficus on the Campus of Universitas Lambung Mangkurat, Banjarmasin, Indonesia - Muhammad Farhan Azhari; Mochamad Arief Soendjoto; Aminuddin Prahatama Putra (IKIP Mataram, 2024)
Campus of Universitas Lambung Mangkurat (ULM) Banjarmasin covering an area of 50.78 ha stands on wetland and is a Ficus habitat. However, what species of this genus grow and develop on this campus have never been documented. This research aimed to inventory species from the genus Ficus, map their distribution and analyze their diversity. Species data was collected through exploration. Species were identified qualitatively or quantitatively based on the morphological characters of stems, leaves, syconium, and roots. The distribution of each species was mapped, the number of individuals counted, and diversity analyzed. Seven species were found, namely F. benjamina, F. kurzii, F. microcarpa, F. elastica, F. natalensis subsp. leprieurii, F. racemosa, and F. trichocarpa. The number of individuals varied from 1 to 53 and they were evenly distributed on campus. The overall density of Ficus was 2.09 individuals/ha and the diversity index was 1.31. Data on morphological characters can be developed as teaching materials, while density and diversity indices become basic data for monitoring the development of Ficus on campus.